Exploring the Spiritual Struggles of God’s Servant in the Book of Jonah - Sia Kok Sin; Mark Simon (Sekolah Tinggi Theologia Jaffray, 2022)
This article focuses on the spiritual struggles of Jonah, as narrated in the book bearing his name. While negative evaluations of Jonah's character have dominated recent scholarly work (for example, as a disobedient, stubborn, nationalistic prophet or anti-hero), this article argues that such categorizations are too simplistic and flat. Jonah is, instead, a complex, round character who dares to disobey and argue with God in the course of his struggle to understand and respond to God's attributes and purposes. Throughout Jonah's book, we see God's patience and mercy at work as he commissioned, disciplined, rescued, recommissioned, and educated Jonah. The article includes an inductive summary of the words and actions of Jonah, a literature review, a re-reading of the text in dialogue with scholarly voices focused on the spiritual struggle of the prophet, and a discussion of key pastoral implications for the calling, discernment and character formation of those in Christian ministry.